Homologous recombination and retention of a single form of most genes shape the highly chimeric mitochondrial genome of a cybrid plant - Sánchez Puerta, María Virginia (2015)
The structure and evolution of angiosperm mitochondrial genomes are driven by extremely high rates of recombination and rearrangement. An excellent experimental system for studying these events is offered by cybrid plants, in which parental mitochondria usually fuse and their genomes recombine. Little is known about the extent, nature and consequences of mitochondrial recombination in these plants. We conducted the first study in which the organellar genomes of a cybrid – between Nicotiana tabacum and Hyoscyamus niger – were sequenced and compared to those of its parents. This cybrid mitochondrial genome is highly recombinant, reflecting at least 30 crossovers and five gene conversions between its parental genomes. It is also surprisingly large (41% and 64% larger than the parental genomes), yet contains single alleles for 90% of mitochondrial genes. Recombination produced a remarkably chimeric cybrid mitochondrial genome and occurred entirely via homologous mechanisms involving the double-strand break repair and/or break-induced replication pathways. Retention of a single form of most genes could be advantageous to minimize intracellular incompatibilities and/or reflect neutral forces that preferentially eliminate duplicated regions. We discuss the relevance of these findings to the surprisingly frequent occurrence of horizontal gene – and genome – transfer in angiosperm mitochondrial DNAs.